CT-guided percutaneous radiofrequency ablation of osteoid osteoma: Our experience in 87 patients - Chahal, Anurag; Rajalakshmi, Prathiba; Khan, Shah A; Rastogi, Shishir; Srivastava, Deep N; Gamanagatti, Shivanand (Indian Journal of Radiology and Imaging, 2017)
Purpose: To evaluate the technical and clinical success of radiofrequency ablation of osteoid osteoma and analyze the factors responsible for clinical success. We also tried to investigate the role of follow-up computed tomography (CT) imaging. Materials and Methods: This is a prospective study approved by the institute's ethics committee involving 87 patients with appendicular osteoid osteoma. CT-guided radio frequency ablation was performed using a bipolar ablation system. Patients were followed up over 15.4 (4–24) months for pain, and clinical success/failure was determined using established criteria. Patients with clinical failure were taken for repeat ablation. Follow-up CT was obtained at 6 months and correlated with clinical success. Procedural scans were later reviewed for technical success in a blinded manner and correlated with clinical success along with other imaging and patient characteristics. Results: Mean pre-procedure visual analog scale (VAS) score was 7.0 ± 0.8. Primary success rate after single session was 86.2%(75/87 patients), and overall success rate after one/two sessions was 96.6%(84/87). No major complications were noted. Technical success rate was 89.7%(78/87). All 9 patients who had a suboptimal needle positioning had recurrence where as three patients had recurrence despite technical success. None of the imaging characteristics or history of prior intervention was significantly associated with clinical success. Follow-up CT showed advanced bone healing in 48 lesions, and was confined to the treatment success group. Alternately, minimal/absent bone healing was seen in all (12) patients of primary treatment failure and 27 patients with treatment success. Conclusions: CT-guided percutaneous radio frequency ablation is a safe and highly effective treatment for osteoid osteomas even in recurrent and residual cases. Technical success is the most important parameter affecting the outcome. Post radio frequency ablation CT findings have a good positive but a poor negative predictive value in prognostication.
Keywords: Interventional radiology; osteoid osteoma; therapy